Developing Kinesemiotics: Challenges and solutions using the Functional Grammar of Dance - Maiorani, Arianna; Liu, Chun (Frontiers in Communication, 2022)
16 This article aims at testing the applicability and the possibility of adaptation of the Functional 17 Grammar of Dance, which is at the core of the development of the new interdisciplinary 18 research area called Kinesemiotics. As a model of analysis for movement-based 19 communication, the Functional Grammar of Dance has already been used for the analysis of 20 classical ballet choreography, and it is currently employed in a collaborative research project 21 involving the authors of this article and their research group at Loughborough University in 22 the UK, the University of Bremen in Germany, and the English National Ballet. The testing 23 opportunity is provided by the challenging analysis of an iconic choreography of the 20th 24 century: Lamentation, a solo piece created by Martha Graham. The analysis will show the 25 applicability of the theory and the adaptability of the model of analysis, and it will also provide 26 examples of the way a new type of annotation based on this grammar has been created and 27 applied using the ELAN annotation software. The use of ELAN includes the implementation of 28 a specifically compiled controlled vocabulary providing labels for coding the materiality, 29 structure and semantics of dance discourse systematically.